2020
DOI: 10.3390/ijerph17218020
|View full text |Cite
|
Sign up to set email alerts
|

PFAS Environmental Pollution and Antioxidant Responses: An Overview of the Impact on Human Field

Abstract: Due to their unique properties, perfluorinated substances (PFAS) are widely used in multiple industrial and commercial applications, but they are toxic for animals, humans included. This review presents some available data on the PFAS environmental distribution in the world, and in particular in Europe and in the Veneto region of Italy, where it has become a serious problem for human health. The consumption of contaminated food and drinking water is considered one of the major source of exposure for humans. Wo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 311 publications
(501 reference statements)
2
39
0
Order By: Relevance
“…Since PFAS can interact with many molecular components of the cell, they can also interfere with different metabolic pathways [ 23 , 24 ], leading to an increase in ROS production and pathologies such as immunotoxicity, neurotoxicity, and alterations of the reproductive system [ 25 ]. It has been shown that PFAS can also cause endocrine disruption and alteration of lipid metabolism [ 3 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since PFAS can interact with many molecular components of the cell, they can also interfere with different metabolic pathways [ 23 , 24 ], leading to an increase in ROS production and pathologies such as immunotoxicity, neurotoxicity, and alterations of the reproductive system [ 25 ]. It has been shown that PFAS can also cause endocrine disruption and alteration of lipid metabolism [ 3 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS) have been among the first to be detected in human blood and in the environment and are considered some of the most widespread PFAS, as shown in several studies [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cells, oxidative stress may occur when ROS production exceeds the antioxidant defence system, causing the peroxidation of membrane lipids, damage to DNA, proteins, and enzymes, and the activation of apoptotic and/or necrotic processes [ 38 ]. Oxidative stress can be promoted by exposure of the organisms to a variety of environmental contaminants, including PFAS [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the extremely strong C-F bond leading to their high stability and resistance to thermal and (bio)chemical degradation [2][3][4]. Due to their unique properties, PFASs have been widely employed in everyday products and industrial formulations with many different applications from non-stick coatings (e.g., cookware and food packaging) to fire-fighting foams, pesticides, and cosmetics since the 1940s [5]. At the same time, these characteristics of PFASs make them environmentally persistent, with the potential to undergo long-range transport and damage living organisms [6,7].…”
Section: Introductionmentioning
confidence: 99%